Optimal laser control of molecular photoassociation along with vibrational stabilization - de Lima, Emanuel F. [UNESP]; Ho, Tak-San; Rabitz, Herschel (Elsevier B.V., 2011)
This work explores the optimization of laser pulses for the control of photoassociation and vibrational stabilization. Simulations are presented within a model system for the electronic ground-state collision of O + H. The goal is to drive the transition from a wavepacket representing the colliding atoms to the vibrational ground level of the diatomic molecule. The optimized fields resulting from two distinct trial pulses are analyzed and compared. Very high yields were obtained in the molecular vibrational ground-level. (C) 2010 Elsevier B.V. All rights reserved.